A Brief Review On Role Of Dinacharya In Enhancement Of Vyadhikshamatva - Sharma, Sakshi; Sharma, Anita; Mishra, Pramod Kumar (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda is the science of life. Ayurveda is the science which emphasize on prevention of diseases more than cure of disease. It is an absolute science of lifestyle. In Ayurvedic classics Dinacharya i.e. “practice of daily routine” has been described as the correct sequence of routine one should follow to get a healthy long life. Dinacharya when followed as per the rules leads to balance in tridosha (i.e. vata, pitta , kapha ) and in this way directly affect the biological clock & Circadian rhythms of body. A well-practiced Dinacharya results in good balance between tryoupstambha which synchronize with Dhatu-Pakka & Dhatu poshan and in formation of Oja which is the main component behind Vyadhikshamatv (immunity) in Ayurved. Here an attempt has been made to present Ayurvedic concept Dinacharya in enhancement of immunity.